An?lise de sinais ECG usando transformada Wavelet com pulso DNAx - Moraes, Matheus Cardoso (2008)
The purpose of this work is to measure and establish the benefits of the Wavelet Transform (WT) , using the DNAx pulses as mother wavelets at the patterns recognition in ECG signals. It was used 50 patients divided in 9 different pathological groups, and one more group of health patients. Only one cardiac cycle from the lead I was used as a reference for each of the patient. At the first test, time correlation was used to measure the similarity between the cardiac cycles of the group of patients with Myocardial Infarction anterior, and after between this group and every group of this work. On the second test, the similarity was estimated using the bi-dimensional cross correlation between the WT coefficients of the cardiac cycles. The transformations were calculated using the two traditional wavelets and others obtained by a technique called DNAx created and patentiated by Caputo. The test comparison showed that, in almost the totality of the cases, the WT associated to the DNAx pulse obtained good results, and in some cases better than the traditional functions.